Proceedings of Narrow-Line Seyfert 1 Galaxies and Their Place in the Universe — PoS(NLS1) 2011
DOI: 10.22323/1.126.0024
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of powerful relativistic jets in narrow-line Seyfert 1 galaxies

Abstract: In 2008, the Fermi Gamma-ray Space Telescope has revealed -for the first time -high-energy (E >100 MeV) γ rays from a few Narrow-Line Seyfert 1 Galaxies (NLS1s). Later, in 2009 and 2010, two multifrequency campaigns on one of these sources, PMN J0948+0022 (z = 0.585), definitely confirmed the presence, in sources of this type, of a relativistic jet very similar and with comparable power to those in blazars. However, these sources are neither blazars nor radio galaxies, as proven by their optical spectrum and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 111 publications
3
47
0
Order By: Relevance
“…The parent samples were restricted to only radio-loud objects from Komossa et al (2006);Zhou et al (2006); Yuan et al (2008);Foschini (2011), which were slightly different from ours including radio-quiet ones as well. Six radio-quiet objects are included in our sample (log RL < 1, see Col. (7) in Table 1).…”
Section: Samplementioning
confidence: 92%
“…The parent samples were restricted to only radio-loud objects from Komossa et al (2006);Zhou et al (2006); Yuan et al (2008);Foschini (2011), which were slightly different from ours including radio-quiet ones as well. Six radio-quiet objects are included in our sample (log RL < 1, see Col. (7) in Table 1).…”
Section: Samplementioning
confidence: 92%
“…In the case of radio-loud NLS1, that have been mentioned in the introduction, their radio power comparable to PKS 1814-637 (see e.g. Yuan et al 2008;Foschini 2011, and references therein) is likely due to their radio emission is dominated by a beamed jet emission. Furthermore, in general the host galaxies of radio-loud NLS1 have not been yet well characterised and, therefore, it is not clear that these object are host by disk galaxies.…”
Section: Link To Seyfert Galaxiesmentioning
confidence: 98%
“…Furthermore, in general the host galaxies of radio-loud NLS1 have not been yet well characterised and, therefore, it is not clear that these object are host by disk galaxies. Two examples (see Zhou et al 2007;Foschini 2011) suggest that this could be the case at least for some of them. If this is confirmed for a larger sample, it may indicate a possible, interesting link between this group of object and objects like PKS 1814-637.…”
Section: Link To Seyfert Galaxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…NLS1s have many properties associated with weak or absent jets (e.g., Lacy et al 2001;Véron-Cetty & Véron 2001): they lie at the low end of the AGN black hole mass range (10 5 −10 8 M ⊙ ; e.g., Zhou et al 2006), accrete at a substantial fraction of the Eddington limit (e.g., Boller et al 1996), and are likely found in spiral or disk host galaxies (Ohta et al 2007). However, about 7% are radio loud (Komossa et al 2006) and among these, evidence of jets in these sources has been found, including from Ackermann et al (2011) or Foschini (2011.…”
Section: Introductionmentioning
confidence: 99%